Jejunal wall delivery of insulin via an ingestible capsule in anesthetized swine—A pharmacokinetic and pharmacodynamic study. Issue 5 (3rd October 2019) - Hashim, Mir; Korupolu, Radhika; Syed, Baber; Horlen, Kyle; Beraki, Simret; Karamchedu, Padma; Dhalla, Arvinder K.; Ruffy, Rodolphe; Imran, Mir
Abstract: Biotherapeutic agents must be administered parenterally to obtain therapeutic blood concentrations, lowering patient compliance and complicating care. An oral delivery platform (ODP) was developed to deliver drugs into the small intestinal wall. This proof‐of‐concept study was performed in 17 anesthetized, laparotomized swine. In 8 swine weighing 17.4 ± 1.2 kg (mean ± SEM), 20 IU of recombinant human insulin (RHI) were auto‐injected into the jejunal wall by placing the ODP inside the jejunum via an enterotomy. In 9 control swine weighing 17.0 ± 0.4 kg, 20 IU of RHI were injected subcutaneously. In both groups, under a 60‐80 mg/dL euglycemic glucose clamp, blood glucose was measured with a handheld glucometer and serum insulin was measured using ELISA, at 10‐minute intervals between −20 and +420 minutes after RHI delivery. The peak serum concentration of RHI was 517 ± 109 pmol/L in the ODP and 342 ± 50 pmol/L in the subcutaneous group (ns). The areas under the insulin concentration curves (83 ± 18 and 81 ± 10 nmol/L·min) were also similar in both groups. The mean time to peak serum concentration of insulin was 139 ± 42 minutes in the ODP and 227 ± 24 minutes in the subcutaneous group (ns). In conclusion, (a) The bioactivity of RHI was preserved after its delivery into the jejunal wall, (b) the intrajejunal route delivered insulin as rapidly and physiologically as the subcutaneous route, and (c) these pharmacokinetic and pharmacodynamic characteristics of RHI after intrajejunal delivery suggest that drugs currently administered parenterally, such as basal insulin, could be successfully delivered into the proximal intestinal wall via the ingestible capsule.